2018
DOI: 10.1016/j.rpor.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Application of an incident taxonomy for radiation therapy: Analysis of five years of data from three integrated cancer centres

Abstract: The application of a taxonomy developed for radiation therapy enhances incident investigation and facilitates strategic interventions. The practice appears to be effective in our institution and contributes to the safety culture. The ratio of near miss to actual incidents could serve as a possible measure of incident reporting culture and could be incorporated into large scale incident reporting systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…That year saw the implementation of daily image guided radiation therapy (IGRT) prior to treatment delivery. The impact of IGRT in reducing the severity of errors is reported by Greenham et al [21], as this technology identifies errors prior to treatment delivery rather than after the treatment is delivered, reducing the potential severity of the incident to the patient. This is reflected a decrease in reported SAC scores since 2013.…”
Section: Discussionmentioning
confidence: 98%
“…That year saw the implementation of daily image guided radiation therapy (IGRT) prior to treatment delivery. The impact of IGRT in reducing the severity of errors is reported by Greenham et al [21], as this technology identifies errors prior to treatment delivery rather than after the treatment is delivered, reducing the potential severity of the incident to the patient. This is reflected a decrease in reported SAC scores since 2013.…”
Section: Discussionmentioning
confidence: 98%
“…Their ratio of near miss to actual incident was 3:1. Greenham et al 14 reported a ratio of approximately 2:1. Holmberg and McClean 44 reported a higher ratio of 14:1.…”
Section: Measuring Safety Culture and Relative Patient Safetymentioning
confidence: 98%
“…The complex nature of radiation oncology requires an incident to be assessed, triaged and managed according to additional taxonomy, such as the degree of dosimetry variance from that prescribed/intended, clinical impact and consequence. General healthcare reporting systems have previously been reported as too broad/blunt for such analysis 11,14 …”
Section: Incident Reporting Terminology and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations